Uji Aktivitas Antidiabetes Ekstrak Teh Hitam dan Teh Hijau secara In Vitro Menggunakan Metode Inhibisi Enzim α-Glukosidase - Diana Holidah; Yasmin Yasmin; Fransiska Maria Christianty (UPT Percetakan dan Penerbitan Universitas Jember, 2018)
Diabetes mellitus is a group of metabolic diseases characterized by hyperglycemia. Carbohydrates are metabolized into glucose, in gastrointestinal tract than absorbed into the bloodstream and increase blood glucose level. This absorption process is catalyzed by α-glucosidase enzyme. Previous studies showed that tea (Camellia sinensis) extract have antidiabetic activity in mice induced by streptozotocin. The aim of this study was to compared the in vitro activity of tea extract in inhibiting α-glucosidase. Black tea and green trea extracts were tested for α-glucosidase inhibitory activity. Acarbose was used as positive control. IC50 extract was 54.86 µg/mL for black tea and 44.79 µg/mL for green tea. This study showed that inhibitory effect of green tea was higher than black tea. Keywords: black tea, green tea, diabetes mellitus, α-glucosidase